Deep pain sensitivity is correlated with oral-health-related quality of life but not with prosthetic factors in complete denture wearers - COSTA, Yuri Martins (J Appl Oral Sci, 2015)
Low pressure Pain Threshold (PPT) is considered a risk factor for Temporomandibular Disorders (TMD) and is influenced by psychological variables. OBJECTIVES: To correlate deep pain sensitivity of masticatory muscles with prosthetic factors and Oral-Health-Related Quality of Life (OHRQoL) in completely edentulous subjects. MATERIAL AND METHODS: A total of 29 complete denture wearers were recruited. The variables were: a) Pressure Pain Threshold (PPT) of the masseter and temporalis; b) retention, stability, and tooth wear of dentures; c) Vertical Dimension of Occlusion (VDO); d) Oral Health Impact Profile (OHIP) adapted to orofacial pain. The Kolmogorov-Smirnov test, the Pearson Product-Moment correlation coefficient, the Spearman Rank correlation coefficient, the Point-Biserial correlation coefficient, and the Bonferroni correction (α=1%) were applied to the data. RESULTS: The mean age (standard deviation) of the participants was of 70.1 years (9.5) and 82% of them were females. There were no significant correlations with prosthetic factors, but significant negative correlations were found between the OHIP and the PPT of the anterior temporalis (r=-0.50, 95% CI-0.73 to 0.17, p=0.005). DISCUSSION: The deep pain sensitivity of masticatory muscles in complete dentures wearers is associated with OHRQoL, but not with prosthetic factors.